Exploring the ethical and aesthetic representations of wetlands in literary texts: a comparative ecocritical study - Pradhan, Swapnit; Kumar, Nagendra (Penerbit Universiti Kebangsaan Malaysia, 2024)
Literary texts, often products of social structures, influence the way people live and shape society. They affect the way we view and interact with living beings as well as non-living elements. Texts possess great potential to fashion people's geographical imagination. Wetlands such as swamps, marshes, and mangrove forests, for example, have varied significances in different temporal and spatial spectrums, but critical scholarship around ethics and representation of wetlands is largely unexplored. This paper, therefore, will primarily seek to analyse textual representations of wetlands in John Bunyan’s Pilgrim’s Progress (1890), H. D. Thoreau’s Walking (1997), Aldo Leopold’s Marshland Elegy (2001), Amitav Ghosh’s Gun Island (2019), and Sarah Joseph’s Gift in Green (2011). By comparing and contrasting these depictions by writers from the Global North and Global South across centuries, we seek to demarcate a clear line of distinction as well as overlaps in the behaviour and feelings of human beings towards the wetlands. The paper emphasises ethical and aesthetic representations of wetlands through the lenses of ecocritical and bioregional theories of Rob Nixon, Simon Estok, and Tom Lynch. Therefore, socio-political analysis and cultural significance conveyed by these depictions may present insights concerning resentment, adoration, aestheticism, commodification, survival, divinity, and fear.